The Application of WIG (Wing-In-Ground-Effect) As a More Cost Effective Transportation in the Indonesian Archipelago - Edi, Prasetyo (Institut Teknologi Dirgantara Adisutjipto, 2020)
Current trends in the design of transport aircraft have shown that in order to be economically viable and competitive it is necessary to investigate technologies that can give an improvement in performance and operational flexibility goal, but must be shown to be cost effective. The current competitive environment forces the potential customers to buy advanced technology aircraft and requires manufacturers to provide more operational flexibility, without drastic performance penalties. This is a challenging task, which might be solved by the use of new technologies. It is believed that the application of a WIG (Wing-in-Ground-Effect) would assist in achieving such a task. This paper describes an investigation aimed to examine the suitability of a WIG concept as a more cost effective transportation in the Indonesian archipelago. This work is unique in terms of application in the Indonesian archipelago. The paper describes the phenomenon of WIG and outlines the benefits and penalties of WIG. It then discusses the possibility of the application of WIG to NKRI. It concludes with a discussion of the results and recommendations for future work.